Electrochemical Surface Biofunctionalization of Titanium through Growth of TiO2 Nanotubes and Deposition of Zn Doped Hydroxyapatite; Coatings; Vol. 12, iss. 1 - Vranceanu D. M. Diana Maria; Ungureanu E. Elena; Ionescu I. C. Ionut; Parau A. C. Anca Constantina; Kiss A. E. Adrian; Vladesku A. Alina; Cotrut C. M. Cosmin (2022, 2022)
Title screen